2001
DOI: 10.1046/j.1365-2249.2001.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of CC- and CXC-chemokine receptors on leucocyte subsets in inflammatory joint diseases

Abstract: SUMMARYChemokine receptors play a crucial role in the recruitment of leucocyte subsets into inflamed tissue. Using FACS analysis we have studied the surface expression of different CC-and CXC-chemokine receptors on synovial fluid (SF) and peripheral blood leucocytes from 20 patients with various forms of arthritis. In the SF the majority T cells stained positive for CCR5 (93%) and CCR2 (57%), compared to the peripheral blood (36% and 25%). In addition, most of the T cells expressed CXCR4 in both compartments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 46 publications
6
47
1
2
Order By: Relevance
“…While some authors were unable to detect expression of CXCR4 [6,7], others have described binding of SDF-1 § , SDF-1 § -induced Ca 2+ flux and migration [8][9][10]. We have detected a clear expression of CXCR4 on neutrophils from the synovial fluid of patients with different inflammatory joint diseases, whereas CXCR4 was hardly detectable in the peripheral blood of patients or normal blood donors, suggesting that CXCR4 on neutrophils could be functionally relevant in the setting of inflammation [11]. Therefore we further investigated the regulation and function of CXCR4 on neutrophils.…”
Section: Introductioncontrasting
confidence: 51%
“…While some authors were unable to detect expression of CXCR4 [6,7], others have described binding of SDF-1 § , SDF-1 § -induced Ca 2+ flux and migration [8][9][10]. We have detected a clear expression of CXCR4 on neutrophils from the synovial fluid of patients with different inflammatory joint diseases, whereas CXCR4 was hardly detectable in the peripheral blood of patients or normal blood donors, suggesting that CXCR4 on neutrophils could be functionally relevant in the setting of inflammation [11]. Therefore we further investigated the regulation and function of CXCR4 on neutrophils.…”
Section: Introductioncontrasting
confidence: 51%
“…CCR1 was only found on a minority of PMNs in both the peripheral blood and SF, and there were no significant differences in CCR1 expression between these groups (21). Neither CCR2 nor CCR5 expression was observed on infiltrating PMNs in RA (21). Here we show that all PMNs in the SF of RA patients express CCRL2.…”
Section: Discussionmentioning
confidence: 52%
“…A previous study demonstrated that joint-infiltrating PMNs in RA downregulate CXCR1 and CXCR2 and up-regulate CXCR4 (21). CCR1 was only found on a minority of PMNs in both the peripheral blood and SF, and there were no significant differences in CCR1 expression between these groups (21). Neither CCR2 nor CCR5 expression was observed on infiltrating PMNs in RA (21).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Data on CCR2 expression in humans and results from studies of CCR2-deficient mice (2-4) support the blockade of CCR2 as an effective strategy in the treatment of multiple sclerosis and diabetes. In patients with rheumatoid arthritis, we and other investigators have found an increased frequency of CCR2ϩ cells in the synovial fluid and synovial tissue (5)(6)(7). In addition, increased levels of the CCR2 ligand monocyte chemoattractant protein 1 (MCP-1; CCL2) were found in patients with rheumatoid arthritis (8).…”
mentioning
confidence: 71%